PERANAN PEMBELAJARAN KONSEP HUKUM PERDATA UNTUK MENINGKATKAN KEBERMAKNAAN PENDIDIKAN KEWARGANEGARAAN - Ayu Vijaya Laksmi, Dyah (Berajah Journal, 2025)
One of the functions of citizenship education is as legal education for students. It is felt that the function of citizenship education as legal education is not optimal. The aim of this research is to determine the role of learning civil law concepts to increase the meaningfulness of citizenship education. This research approach is a qualitative approach. Based on the research results, it shows that the function and aim of Citizenship Education is to open up the widest possible opportunities for citizens, to express their commitment and carry out an active role, to learn to mature themselves, especially regarding legal, moral and functional relationships between citizens and state organizational units and other public institutions. The figure of a good citizen that Citizenship Education aims to produce is an independent citizen who is not a burden on anyone, who involves himself in learning activities, understands the outline of history, ideals, and goals of the state, and is productive by contributing to advancing order, security, the economy and general welfare.